Let S and T denote the two finite sums,
S = 1 + x + x ² + x ³ + … + x ᴺ
T = 1 - x + x ² - x ³ + … + (-x) ᴺ
• If both S = 8 and T = 8 as N goes to infinity:
Then
xS = x + x ² + x ³ + x ⁴ + … + x ᴺ⁺¹
-xT = -x + x ² - x ³ + x ⁴ + … + (-x) ᴺ⁺¹
so that
S - xS = 1 - x ᴺ⁺¹ ==> S = (1 - x ᴺ⁺¹)/(1 - x)
and similarly,
T = (1 - (-x) ᴺ⁺¹)/(1 + x)
For both sums, so long as |x| < 1, we have
lim [N → ∞] S = 1/(1 - x)
lim [N → ∞] T = 1/(1 + x)
Then if both sums converge to 8, this happens for
S : 1/(1 - x) = 8 ==> x = 7/8
T : 1/(1 + x) = 8 ==> x = -7/8
• If the sum S + T = 8 as N goes to infinity:
From the previous results, we have
1/(1 - x) + 1/(1 + x) = 8 ==> x = ±√3/2